Antibiotic resistance prediction for Mycobacterium tuberculosis from genome sequence data with Mykrobe - Hunt, M; Bradley, P; Lapierre, SG; Heys, S; Thomsit, M; Hall, MB; Malone, KM; Wintringer, P; Walker, TM; Cirillo, DM; Comas, I; Farhat, MR; et al. (F1000Research, 2019)
Two billion people are infected with Mycobacterium tuberculosis, leading to 10 million new cases of active tuberculosis and 1.5 million deaths annually. Universal access to drug susceptibility testing (DST) has become a World Health Organization priority. We previously developed a software tool, Mykrobe predictor, which provided offline species identification and drug resistance predictions for M. tuberculosis from whole genome sequencing (WGS) data. Performance was insufficient to support the use of WGS as an alternative to conventional phenotype-based DST, due to mutation catalogue limitations.